Development of gatifloxacin-loaded cationic polymeric nanoparticles for ocular drug delivery. (17th February 2016) - Duxfield, Linda; Sultana, Rubab; Wang, Ruokai; Englebretsen, Vanessa; Deo, Samantha; Swift, Simon; Rupenthal, Ilva; Al-Kassas, Raida
Abstract: The present investigation aimed at improving the ocular bioavailability of gatifloxacin by prolonging its residence time in the eye and reducing problems associated with the drug re-crystallization after application through incorporation into cationic polymeric nanoparticles. Gatifloxacin-loaded nanoparticles were prepared via the nanoprecipitation and double emulsion techniques. A 50:50 Eudragit® RL and RS mixture was used as cationic polymer with other formulation parameters varied. Prepared nanoparticles were evaluated for size, zeta potential, and drug loading. An optimized formulation was selected and further characterized for in vitro drug release, cytotoxicity, and antimicrobial activity. The double emulsion method produced larger nanoparticles than the nanoprecipitation method (410 nm and 68 nm, respectively). Surfactant choice also affected particle size and zeta potential with Tween 80 producing smaller-sized particles with higher zeta potential than PVA. However, the zeta potential was positive at all experimental conditions investigated. The optimal formulation produced by double emulsion technique and has achieved 46% drug loading. This formulation had optimal physicochemical properties with acceptable cytotoxicity results, and very prolonged release rate. The particles antimicrobial activities of the selected formulation have been tested against Escherichia coli, Pseudomonas aeruginosa, and Staphylococcus aureus and showed prolonged antimicrobial effect for gatifloxacin.